Kinerja Perusahaan Perbankan (Studi Perbandingan Dua Periode Krisis di Indonesia) - lubis, nurhayani (Jurnal Daya Saing, 2016)
Abstract: The purpose of this study was to determine whether there are differences in the Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Return on Assets (ROA), Operating Expenses to Operating Income (ROA), Loan to Deposit Ratio (LDR), and stock returns in the two periods of crisis in Indonesia. Namelyin 1997and 2008.The sample inthis study are allfromthe1993-2010bankingcompany. There are fourhypothesesto be testedin this study. This study using t test SPSS to analyzed data. Keywords: Economic Crisis, Stock Return, CAR, NIM, ROA, BOPO, LDR